México y Cuba. Del Frente Popular a la Unidad Nacional - Massón Sena, Caridad (Departamento de Estudos Latino-Americanos - ELA, 2018)
Mexico and Cuba: from Popular Fronts to National Unity examine the various consequences of the implementation of shifting and contradictory policies of the Communist International from 1935 to 1943 in both countries.